Plasmodiophora brassicae resting spore dynamics in clubroot resistant canola (Brassica napus) cropping systems. (12th October 2018) - Ernst, T. W.; Kher, S.; Stanton, D.; Rennie, D. C.; Hwang, S. F.; Strelkov, S. E.
Abstract : The soilborne pathogen Plasmodiophora brassicae, causal agent of clubroot of canola ( Brassica napus ), is difficult to manage due to the longevity of its resting spores, ability to produce large amounts of inoculum, and the lack of effective fungicides. The cropping of clubroot resistant (CR) canola cultivars is one of the few effective strategies for clubroot management. This study evaluated the impact of the cultivation of CR canola on P. brassicae resting spore concentrations in commercial cropping systems in Alberta, Canada. Soil was sampled pre‐seeding and post‐harvest at multiple georeferenced locations within 17 P. brassicae ‐infested fields over periods of up to 4 years in length. Resting spore concentrations were measured by quantitative PCR analysis, with a subset of samples also evaluated in greenhouse bioassays with a susceptible host. The cultivation of CR canola in soil with quantifiable levels of P. brassicae DNA resulted in increased inoculum loads. There was a notable lag in the release of inoculum after harvest, and quantifiable P. brassicae inoculum peaked in the year following cultivation of CR canola. Rotations that included a ≥2‐year break from P. brassicae hosts resulted in significant declines in soil resting spore concentrations. A strong positive relationship was found between the bioassays and qPCR‐based estimates of soil infestation. Results suggest that CR canola should not be used to reduce soil inoculum loads, and crop rotations in P. brassicae infested fields should include breaks of at least 2 years away from B. napus, otherwise the risk of selecting for virulent pathotypes may increase.